2020
DOI: 10.26633/rpsp.2020.116
|View full text |Cite
|
Sign up to set email alerts
|

Risk of Zika virus-associated birth defects in congenital confirmed cases in the Brazilian Amazon

Abstract: Objective. To establish the risk of microcephaly in neonates born to women infected with ZIKV during pregnancy. Methods. A cohort of laboratory-confirmed ZIKV cases of congenital infections (109 mothers infected during pregnancy and 101 newborns) among 308 suspect cases was followed in Belem, Pará, Brazil, from October 2015 to December 2017. Results. A microcephaly risk of 1.98% (95% CI 0.54-6.93%) was found, or 2 cases among the 101 neonates infected with ZIKV during pregnancy. 72% of the pregnant women had Z… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
3
0

Year Published

2023
2023
2023
2023

Publication Types

Select...
2
1

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(3 citation statements)
references
References 13 publications
0
3
0
Order By: Relevance
“…In addition, the authors suggest that the protective effect against ZIKV induced by multiple prior DENV infections could prevent congenital Zika syndrome (PEDROSO et al, 2019;OLIVEIRA et al, 2020). This information is useful for clinical health practice, as this study identified a reasonable number of pregnant natives who were separately infected with dengue, Zika, and chikungunya.…”
Section: Discussionmentioning
confidence: 86%
“…In addition, the authors suggest that the protective effect against ZIKV induced by multiple prior DENV infections could prevent congenital Zika syndrome (PEDROSO et al, 2019;OLIVEIRA et al, 2020). This information is useful for clinical health practice, as this study identified a reasonable number of pregnant natives who were separately infected with dengue, Zika, and chikungunya.…”
Section: Discussionmentioning
confidence: 86%
“… 5 The follow-up of cohorts of pregnant women allowed estimating the risk for microcephaly, abnormalities of the Central Nervous System (CNS) diagnosed by imaging, ophthalmologic and audiologic alterations and other birth defects in children born to Zika virus-infected mothers during pregnancy. 6 7 8 9 10 11 12 13 Although cohort studies have shown similar risks of microcephaly, estimates of the risk of other manifestations were diverse, indicating the need to use other analysis strategies with more robust estimates, such as meta-analysis.…”
mentioning
confidence: 99%
“…5 The follow-up of cohorts of pregnant women allowed estimating the risk for microcephaly, abnormalities of the Central Nervous System (CNS) diagnosed by imaging, ophthalmologic and audiologic alterations and other birth defects in children born to Zika virus-infected mothers during pregnancy. [6][7][8][9][10][11][12][13] Although cohort studies have shown similar risks of microcephaly, estimates of the risk of other manifestations were diverse, indicating the need to use other analysis strategies with more robust estimates, such as meta-analysis.…”
mentioning
confidence: 99%